Rights of the Indigenous Peoples to Self-Government: A Comparative Analysis between New Zealand and Canada - Hind Sebar; Rohaidah Nordin (Faculty of Law, Universitas Jenderal Soedirman, 2021)
Canada and New Zealand are the western liberal democracies settled by a predominantly English-speaking majority. Their legal and constitutional system depends on English common law. Both Canada and New Zealand have a high percentage of indigenous peoples irrespective of the 4% difference in Canada and 15% in New Zealand. Both states rank high in global comparisons of human development. There exist many differences in the rights of self-government of indigenous peoples in both Canada and New Zealand. These distinctions in the application of the self- government right in local and regional level greatly impacts how indigenous peoples put self- government into practice and brings forth significant questions about which version of these applications best serves the interests of indigenous peoples. This is a comparative study that expounds the differences between constitutions of both countries together with the distinctions in the rights of self-government of indigenous peoples. By using the legal combative method to compare constitutions of Canada and New Zealand and their policies regarding rights of self-government of indigenous peoples, this study concludes that with respect to clear constitutional and legislative recognition of the right of self -government Canada is more advanced. Additionally, this study points out significant institutional work differences between indigenous peoples’ self-government rights in both countries. Keywords- Canada; Indigenous peoples; indigenous rights; Native; New Zealand; Self-government.